CXOU J005245.0-722844: Optical period of possible counterpart hints at BeXRB nature of the system - Treiber, H.; Haberl, F.; Vasilopoulos, G.; Bailyn, C. D.; Udalski, A. (2024)
An X-ray outburst was recently detected by the Einstein Probe mission and designated EP J0052.9-7230 (ATel #16631). Swift's S-CUBED survey (Kennea et al. 2018) then localized the event to the X-ray source CXOU J005245.0-722844 and noted that the soft spectrum is consistent with a Be X-ray binary (BeXRB) system with a white dwarf as the compact object (ATel #16633).
Keywords: Binary; Transient